Seizures in the shower: a case report on hot water epilepsy - Dsouza, Glory; Shruti, Hiremath (International Journal of Advances in Medicine, 2024)
An uncommon kind of reflex epilepsy called hot water epilepsy is brought on by bathing in or being near hot water. In this case study, a 43-year-old man with a history of head trauma experiences seizures brought on by exposure to hot water. Concurrent symptoms include giddiness. The best course of treatment for HWE typically involves avoiding lukewarm water in the first place and utilizing either standard AEDs or benzodiazepines for intermittent oral prophylaxis.